Upaya Orang Tua dalam Meningkatkan Minat Shalat Fardhu Pada Anak di Desa Gonilan Kartasura - Shafarania Frizca Amelia; Zaenal Abidin (Journal on Education, 2023)
The entry of the era of globalization and digitalization which is marked by various changes in values has an impact on eroding religious values in carrying out life, including in carrying out fardhu prayers. Parents are required to improve strategies and efforts to increase children's interest in fardhu prayers, so that children still adhere to Islamic values and carry out their obligations, including fardhu prayers. The research aims to find out the efforts made by parents to instill the discipline of fardhu prayers in their children and to identify the obstacles that hinder these efforts. This research is detailed descriptively and uses phenomenology. This research relies on direct information from short interviews with 8 (eight) mothers who are parents. Semi-structured questions and answers were used during the interview. The results of the study show that parents' efforts to increase their children's interest in fardhu prayers in Gonilan Kartasura Village, namely choosing Islamic-based education, being an example or role model (uswatun hasanah), giving gifts (reward), using the help of internet media and technology . Meanwhile, the factors that hinder parents' efforts to motivate children so that they are interested in carrying out their children's obligatory prayers are internal factors (a feeling of laziness in children, especially when watching television and playing cellphones) and external factors (friendship environmental factors).